Edukasi Kesehatan Menari (Menopause Aman dengan Rutin konsumsi Soya) untuk Mengatasi Panas di Wajah pada Wanita Menopause di Puskesmas Sumur Batu - Sanjaya, Riona; Komalasari; Tri Utami, Iis; Kusuma Wardani, Psiari; Selvia, Dita; Puspita Darma, Hanum; Diana Fitri N, Evita; Wardaty, Nahdiyatul; Lestari, Dina; Meitasari, Reza; Dwita, Tamara; Yani, Fitri; Nuraisyah Wuryandari, Vania; Lestari, Ratih (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Menopause is a natural phase in a woman’s life characterized by the cessation of menstruation and a decline in estrogen levels, often accompanied by various complaints, one of which is hot flashes. Hot flashes are vasomotor symptoms that can significantly affect the quality of life of menopausal women. Objective: This community service activity aimed to improve menopausal women’s knowledge about hot flash symptoms and the use of non-pharmacological interventions, particularly the consumption of soy milk containing phytoestrogens as a natural alternative therapy. Method: The education program was conducted on August 1, 2025, at Sumur Batu Community Health Center, Bandar Lampung City, using interactive lectures, group discussions, leaflet distribution, and serving of sy milk preparations. Evaluation through pre-test and post-test instruments showed a significant increase in participants’ knowledge, with the average score rising by 38.28 points. Result: The Wilcoxon statistical test yielded a p-value of 0.000, indicating that the educational intervention had a significant effect on improving participants’ knowledge. This activity also produced an educational product in the form of a leaflet entitled “Menari: Menopause Aman dengan Rutin Konsumsi Soya” and visual documentation for further dissemination. Conclusion: This educational activity proved effective as a promotive and preventive strategy that can be applied in community midwifery services and has the potential to be replicated in other regions. It is expected to serve as an initial step in empowering menopausal women through sustainable nutrition education approaches.